The Potential Development of MSMEs in Celah Covid-19 Turnes an Increased Production of Rambak Crackers, Desa Sawo Kec. Showder Kab. Gresik Jawa Timur - Ruswaji Ruswaji; Sovy Elsariyana (Jurnal Mantik, 2020)
In the business world, the value of success is not only determined by capital and enthusiasm for work. Business actors really need to know the development of technology, management and reliable financial systems and understand the dangers caused by the use of chemical substances when the type of business is in the food sector. It is difficult for the MSME group of rambak cracker to develop because of the many problems faced and unsolved due to the lack of knowledge in the fields mentioned above. Production results are mostly non-uniform in dimensions, appearance or even taste quality. UMKM rambak cracker business group can only be said to survive and pay less attention to a better future and sustainability. From the above conditions, we as academics are very moved to help UMKM partners who are in Sawo Village, Dukun District, Gresik Regency, East Java Province, who are currently in a difficult condition to develop. The solution offered is the method of discussion and observation to identify problems, conduct activities, training workshops with materials on marketing and entrepreneurship management. We also give lectures on the use of hazardous chemicals in food mixtures with the noble aim so that MSME partners are not solely looking for profit but act as good entrepreneurs and care for others. Assistance and monitoring activities are also carried out to determine the extent of the development of their production business and the impact training outcomes as well as facilitating marketing access which is expected to increase capacity building.